Enhancing Active Learning Applications for Google Classroom to Improve Learners’ Academic Achievements and Competencies: A Case Study of Pattani Industrial and Community Education College - Abdullatif, Kawissara; Matayong, Sureena; Witosurapot, Suntorn; Choosawang, Sutitar (JOURNAL OF SOUTHERN TECHNOLOGY, 2024)
Google Classroom has widely benefited educational institutions by developing a learning management system. However, it has been found that there is a lack of functions to promote active learning activities, which has significantly hindered student achievement and performance. This study aims to develop a set of active learning applications for Google Classroom and measure student achievement and core competencies after using the applications. A sample of 42 students was selected from a group of high vocational certificate students who were in their second year, enrolled in a computer programming course at Pattani Vocational College using a quota sampling method. The course focuses on computer programming for electrical control as part of Electrical Power Engineering program. They were divided into experimental and control groups, and were independent of each other. An achievement test, a competency assessment form of the given tasks and teacher observation, and student self-assessment of core competencies were used as instruments in this study. Data analysis was divided into two parts. One is descriptive statistics, including percentages, mean, standard deviation, median, and skewness. The other is inferential statistics, testing hypotheses at the .05 significance level using the Shapiro-Wilk test for normal distribution, t-Test and Mann-Whitney U Test were used to compare the means of two independent populations, and the Sign Test was used to test the difference between two paired populations.It was revealed that 1) there was no significant difference in the pre-test scores of the two groups; 2) the pre- and post-test scores of the experimental group were significantly higher than the control group; and 3) the post-test scores of both groups were higher than the pre-test scores. The teacher assessment revealed that learners’ competencies in all 5 domains were at a very good level. The highest score was in terms of teamwork and collaboration skills accounting for 97.14%, followed by creativity representing 90.48% and problem-solving, communication, computer and information technology skills representing 89.52% respectively. Therefore, it can be concluded that the enhancement of active learning applications for Google Classroom can effectively improve learning outcomes and student competencies.